Construction of Otherwise Isogenic Serotype 6B, 7F, 14, and 19F Capsular Variants of Streptococcus pneumoniae Strain TIGR4 - Trzcinski, Krzysztof (American Society for Microbiology, 2003)
The polysaccharide capsule is the primary virulence factor in Streptococcus pneumoniae. There are at least 90 serotypes of S. pneumoniae, identified based on the immunogenicity of different capsular sugars. The aim of this study was to construct pneumococcal strains that are isogenic except for capsular type. Serotype 4 strain TIGR4 was rendered unencapsulated by recombinational replacement of the capsular polysaccharide synthesis (cps) locus with the bicistronic Janus cassette (C. K. Sung, J. P. Claverys, and D. A. Morrison, Appl. Environ. Microbiol. 67:5190-5196, 2001). In subsequent transformation with chromosomal DNA, the cassette was replaced by the cps locus derived from a strain of a different serotype, either 6B, 7F, 14, or 19F. To minimize the risk of uncontrolled recombinational replacements in loci other than cps, the TIGRcps::Janus strain was “backcross” transformed three times with chromosomal DNA of subsequently constructed capsular type transformants. Capsular serotypes were confirmed in all new capsule variants by the Quellung reaction. Restriction fragment length polymorphism (RFLP) analysis of the cps locus confirmed the integrity of the cps region transformed into the TIGR strain, and RFLP of the flanking regions confirmed their identities with the corresponding regions of the recipient. Transformants had in vitro growth rates greater than or equal to that of TIGR4. All four strains were able to colonize C57BL/6 mice (female, 6 weeks old) for at least 7 days when mice were intranasally inoculated with 6 × 10(6) to 8 × 10(6) CFU. The constructed capsular variants of TIGR4 are suitable for use in studies on the role of S. pneumoniae capsular polysaccharide in immunity, colonization, and pathogenesis.